Advanced LC-MS-based methods to study the co-occurrence and metabolization of multiple mycotoxins in cereals and cereal-based food - Malachová, Alexandra; Stránská, Milena; Václavíková, Marta; Elliott, Christopher T; Black, Connor; Meneely, Julie; Hajšlová, Jana; Ezekiel, Chibundu N; Schuhmacher, Rainer; Krska, Rudolf (Analytical and bioanalytical chemistry, 2018)
Liquid chromatography (LC) coupled with mass spectrometry (MS) is widely used for the determination of mycotoxins in cereals and cereal-based products. In addition to the regulated mycotoxins, for which official control is required, LC-MS is often used for the screening of a large range of mycotoxins and/or for the identification and characterization of novel metabolites. This review provides insight into the LC-MS methods used for the determination of co-occurring mycotoxins with special emphasis on multiple-analyte applications. The first part of the review is focused on targeted LC-MS approaches using cleanup methods such as solid-phase extraction and immunoaffinity chromatography, as well as on methods based on minimum cleanup (quick, easy, cheap, effective, rugged, and safe; QuEChERS) and dilute and shoot. The second part of the review deals with the untargeted determination of mycotoxins by LC coupled with high-resolution MS, which includes also metabolomics techniques to study the fate of mycotoxins in plants.
Keywords: Mycotoxins; Solid Phase Extraction; Edible Grain; jedlá semena; houby; Tandem Mass Spectrometry; vysokoúčinná kapalinová chromatografie; Food Analysis; Liquid chromatography–tandem mass spectrometry; Validation; Metabolomics; mykotoxiny; Fungi; metabolomika; Chromatography, High Pressure Liquid; analýza potravin; tandemová hmotnostní spektrometrie; Liquid chromatography–high-resolution mass spectrometry; Chromatography, Affinity; extrakce na pevné fázi; Fungal secondary metabolites; chromatografie afinitní